The factor inhibiting HIF regulates T cell differentiation and anti-tumour efficacy - Bargiela, David; Cunha, Pedro P.; Veliça, Pedro; Krause, Lena C. M.; Brice, Madara; Barbieri, Laura; Gojkovic, Milos; Foskolou, Iosifina P.; Rundqvist, Helene; Johnson, Randall S. (Frontiers in Immunology, 2024)
The hypoxia-inducible factor (HIF) transcription factors play a key role in T cell activation and their adaptation to physiological changes in oxygen tensions. HIF transcriptional activity is regulated by the asparaginyl hydroxylase, factor inhibiting HIF (FIH). The role of FIH in determining T cell fate and function remains unknown.We generated T cell-specific knockout mice to profile the effects of FIH across a range of HIF and oxygen levels. Our results show that FIH regulates T cell function in a HIF-dependent manner, and is most active at intermediate, physiological oxygen tensions. Loss of FIH in T cells augments in vivo T cell expansion and improves T cell anti-tumour activity in mice. These results support FIH inhibition within T cells as a potential immunotherapy strategy.